Book-tax conformity and reporting behavior: A quasi-experiment - Maria Theresia Evers; Ina Meier; Katharina Nicolay (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2016)
We examine how a comprehensive change in book-tax conformity affects firms' reporting behavior. To this end, we exploit a Reform Act as a quasi-natural experiment which implied a decrease in book-tax conformity in Germany in 2010. In particular, this reform allows firms to exercise tax accounting options independently from financial accounting. Our study builds on a unique dataset of linked individual financial statements and actual tax return data. It covers roughly 150 incorporated firms for the years 2008 to 2012. Exploiting the exceptional change in conformity, we contribute to the ongoing debate on the impact of booktax conformity. Our results show that profitable companies, which have a clear tax sheltering incentive, actually use the newly introduced reporting leeway to manage taxable income downwards. This is especially attributable to companies exploiting favorable tax depreciation rules. Moreover, we find larger opportunistic tax reporting responses for small companies with less complex and predominantly domestic group structures. In addition, we observe that a decrease in book-tax conformity induces a decrease in the general persistence of taxable income, but at the same time gives rise to higher financial earnings persistence. This corroborates our finding of increased tax sheltering activity in post reform years.
urn:nbn:de:bsz:180-madoc-406399
Keywords: H20; H25; K34; M41; 330; book-tax conformity; book-tax differences; tax sheltering; earnings persistence